IMPLEMENTASI MEDIA FLASHCARD DALAM MELATIH KEMAMPUAN MEMBACA PESERTA DIDIK KELAS II MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN TAHUN 2024 - Hasifa Putri, Hanifah; Hasyim Fanirin, Moch.; Humaeroh, Iis (Sindoro: Cendikia Pendidikan, 2024)
This research examines the Implementation of Flashcard Media in Improving Reading Skills of Class II Students of Madrasah Ibtidaiyah Ma'had Al-Zaytun Indramayu. This study focuses on the problem of students who are still not fluent in recognizing letters, reading words, and simple sentences. Furthermore, this study aims to determine how the Implementation of Flashcard Media in Improving Reading Skills of Class II Students of Madrasah Ibtidaiyah Ma'had Al-Zaytun Indramayu. This study uses a mix method with an explanatory sequential research design model. The implementation is carried out sequentially, starting with quantitative and continuing with qualitative. The type of research used is a pre-experiment with a one-group pretest-posttest approach, where researchers only use one class that is given treatment and will undergo two tests, namely the initial test (pretest) and the final test (posttest). The results of the study showed that there was an increase in the reading ability of class II students of Madrasah Ibtidaiyah Ma'had Al-Zaytun which can be proven by the average pretest score of 88.56 and the average posttest score reaching 96.06. The above indicates an increase in class II students of MI Ma'had Al-Zaytun. In the T-test, the Sig. value was obtained at 0.000 which is smaller than 0.05, so Ha is accepted and Ho is rejected. The t-test uses tcount> ttable, which is 5.671> 2.034, which means Ho is rejected and Ha is accepted. This explains that there is a significant difference between the average reading test scores of students before and after the implementation of flashcard learning media. Keywords: implementation, flashcard learning media, reading ability